INFLUENCE OF PARENTAL ROLE AND SCHOOL ENVIRONMENT ON DEPRESSION IN ADOLESCENTS - Astuti, Puji; Setiyani, Astuti; Husni, Ervi; Harumi, Ani Media (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2024)
Depression in adolescents can be caused by the influence of the role of parents and the influence of the role of the school environment. The 2018 Riskesdas results show that almost 5% of teenagers and school children in East Java, especially in Surabaya, 10.8% of the total population of Indonesia suffer from depression. Data from the Ministry of Women's Empowerment and Child Protection (KPPPA) as of July 2020, states that there are more than 3,200 (13%) elementary to high school students in Indonesia with symptoms of mild to severe depressive disorders. The aim of this research is to determine the influence of the role of parents and the role of the school environment on the incidence of depression in adolescents. This type of research is descriptive analytic with a cross sectional approach. The population in this study was 624 teenagers from class VII and VIII who were selected using the simple random sampling technique. The independent variables of this research are the role of parents and the role of the school environment. Dependent variable is depression. Place and time of research at SMPN 3 Surabaya in April 2024. The research instrument is a questionnaire. Data were processed with SPSS for analysis using the Wilcoxon test with a significance level of α 0.05.The results of the research on the influence of the role of parents showed that half of the respondents had a sufficient role and there was an influence on the incidence of depression in adolescents means that there was an influence of the role of parents on the incidence of depression in adolescents. It was found that almost half of the respondents had a sufficient role and had an influence on the incidence of depression in adolescents means that there is an influence of the school environment on the incidence of depression in adolescents.